Detection of Electromyography Signal using Dry and Disposable Electrodes on the Bicep Muscle While Lifting Weights - Amrinsani, Farid; Wakidi, Levana Forra; Suryanta, Made Dwi Pandya; Wulandari, Dessy Tri; Sadiq, Muhammad Tariq (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
One of the biosignals used to identify human muscle impulses is electromyography. Electromyographic signals are often used as input and are designed to help people with disabilities or help the healing process after stroke therapy. According to research, this incident has led to the development of various electromyography module sensor designs to meet different purposes. This research was conducted to make two different electromyography module designs and test these modules simultaneously when the biceps lifted a weight of 3Kg. The aim of this study was to compare the use of disposable and dry electrodes from the two electromyographic sensor module designs that were made. using root mean square (RMS) to find out the difference in tension generated when lifting the barbell. each module detects the biceps signal simultaneously. The biceps are part of the upper limb muscles. Based on the findings of this study, both E1 and E2 electromyography modules with disposable electrodes produced data with a p-value of 0.001766368 less than 0.05. while for the t-test of the two Electromyography modules E1 and E2 with dry electrodes it is 0.001766368 which is less than 0.05. Therefore, it can be concluded that there is a significant difference between the E1 and E2 modules. there is an average amplitude difference of 10mV between E1 and E2 modules when using both types of electrodes. and there is a difference in the average amplitude using dry and disposable electrodes of 30mV. The results of this study can be used to provide insight into the detection of electromyography signals, while the two module designs developed can be applied in future studies to detect electromyography.